The Selection of Freebies and the Preference for Freebie Promotions—A Perspective on Item Characteristics. (1st April 2016) - Liu, Hsin‐Hsien; Chou, Hsuan‐Yi
Abstract: Research on consumer decision making has mainly focused on individual products; however, many products are purchased with other items as part of a promotional package. This paper explores how the characteristics (hedonic versus utilitarian) of the items in freebie promotional packages (e.g., buy one item and get a different item for free) influence consumers' preference for the promotional package. Additionally, the authors examine how the characteristics of the focal item influence consumers' choice of either a hedonic or a utilitarian freebie item. Five experiments, rooted in the concepts of consumer avoidance of overloading negative emotions and motivation to seek hedonic pleasure, show that a package with one utilitarian and one hedonic item generates higher purchase intentions and willingness to pay than a package with either two hedonic or two utilitarian items. Furthermore, consumers who purchase a hedonic (utilitarian) focal item are more likely to choose a utilitarian (hedonic) freebie. These effects exist not only in hypothetical scenarios but also in an incentive‐compatible design. Moreover, the impact of the focal item characteristics on consumer choice of freebie is moderated by acquisition format and time separation. The authors also explore the internal mechanism influencing consumers' freebie choices. The findings have significant implications for both theory and practice. Copyright © 2016 John Wiley & Sons, Ltd.